Tradução, adaptação transcultural e validação do The Northwick Park Neck Pain Questionnaire para o português brasileiro - Almeida, Mariana Quixabeira Guimarães (2020)
Introduction: Neck pain can be defined as pain located in the posterior cervical region up to the upper scapular level. Considering functional disability as an important clinical aspect during the assessment of chronic neck pain, the importance of valid and reliable instruments with methodological sturdiness is emphasized, in order to use in studies and guide clinical practice of healthcare professionals who treat people with chronic neck pain, considering the cultural and idiomatic specificities of Brazilian Portuguese. Objective: The aim of this study was twofold: 1) to perform the translation and cross-cultural adaptation into Brazilian Portuguese of the Northwick Park Neck Pain Questionnaire (NPQ) for individuals with chronic neck pain; 2) to measure the reproducibility, structural validity, construct validity and internal consistency of this new version of the instrument. Methods: One hundred and seventy-nine people with chronic neck pain took part in the study. In order to analyze the structural validity, exploratory and confirmatory factor analysis were used with the following fit indexes: Chi-square (X²), Chi-square divided by degrees of freedom (X²/df), Root Mean Square Error of Approximation (RMSEA), Comparative Fit Index (CFI) and Tucker Lewis Index (TLI). To test the construct validity, Spearman's correlation (rho) was used with the other instruments used in the study: Numerical Pain Scale (NPS), Tampa Scale of Kinesiophobia (TSK), Pain Catastrophizing Scale (PCS) and Neck Disability Index (NDI). A subsample of 84 patients completed the NPQ in two moments in a minimum interval of 7 days and a maximum of 10 days, in order to assess reliability test-retest using the intraclass correlation coefficient (ICC), standard error of measurement (SEM) and minimum detectable change (MDC). The internal consistency of the NPQ was analyzed by Cronbach's alpha. The floor and ceiling effects were also evaluated in the study. Results: The factor analysis identified a one-dimensional structure of the NPQ with adequate fit indexes: X2/gl = 1.09, CFI = 0.99, TLI = 0.99, RMSEA (IC a 90%) = 0.031 (0.000 to 0.145). Adequate reliability was observed for the total NPQ score, with values of ICC of 0.94, SEM of 3.33 points (14.17%) and MDC of 9.22 points (39.27%). Adequate values of internal consistency were also observed, with Cronbach's alpha of 0.76. There were no ceiling and floor effects. Conclusion: The Brazilian version of the NPQ with a one-dimensional structure and 5 items has adequate measurement properties, supporting its use in the clinical context and in research with patients with chronic neck pain.